Channel Capacity Enhancement of MIMO System using Water-Filling Algorithm - et. al., Harsha Gurdasani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The demand for higher speeds continues to grow today. In many circumstances, wireless systems are an effective solution, providing high speeds at a lower cost than cable-based technologies. Bandwidth and power limitations in today's communications systems make MIMO technology indispensable today. Diversity in MIMO applications tends to upgrade the architecture of system for compensation with upgraded hardware and software requirements. This paper work presents an analysis of bit error rate (BER) performance of STBC, Orthogonal-STBC and channel capacity enhancement framework of MIMO system using water-filling algorithm with ML, ZF and MMSE equalization techniques